Radiation Shielding Properties Prediction of Barite used as Small Aggregate in Mortar - Vu, H. Q.; Tran, V. H.; Nguyen, P. T.; Le, N. T. H.; Le, M. T. (Engineering, Technology & Applied Science Research, 2020)
Construction materials used in the nuclear industry used to be mainly heavy materials, including lead plates, radiation-resistant heavy concrete, etc. However, these materials are either toxic after a long time of use (lead) or difficult to construct (radiation-resistant heavy concrete) and their cost is rather high. Therefore, there is a need for the manufacturing of a new kind of material with good radiation resistance, which is light, easy to use, and costs less. Barium is less toxic and more cost-effective than lead. Due to the importance of barium compounds in radiation shielding, the study of gamma radiation interactions within these compounds becomes essential, so the most important part of such a study is the experimental one, which shows the effect of the barite powder in the radiation resistance of the mortar. The research results show that the higher the thickness and percentage of barite powder, the higher is the radiation resistance.